INTERACTION BETWEEN GLYCOGENIN AND GLYCOGEN SYNTHASE - Skurat, Alexander V. (2006)
Glycogen synthase plays a key role in regulating glycogen metabolism. In a search for regulators of glycogen synthase, a yeast two-hybrid study was performed. Two glycogen synthase-interacting proteins were identified in human skeletal muscle, glycogenin-1 and nebulin. The interaction with glycogenin was found to be mediated by the region of glycogenin which contains the 33 COOH-terminal amino acid residues. The regions in glycogen synthase containing both NH(2)- and COOH-terminal phosphorylation sites are not involved in the interaction. The core segment of glycogen synthase from Glu(21) to Gly(503) does not bind COOH-terminal fragment of glycogenin. However, this region of glycogen synthase binds full-length glycogenin indicating that glycogenin contains at least one additional interacting site for glycogen synthase besides the COOH-terminus. We demonstrate that the COOH-terminal fragment of glycogenin can be used as an effective high affinity reagent for the purification of glycogen synthase from skeletal muscle and liver.